Proceedings of the 3rd International Conference on Theory and Practice of Electronic Governance 2009
DOI: 10.1145/1693042.1693076
|View full text |Cite
|
Sign up to set email alerts
|

Issues and strategies for conducting cross-national e-government comparative research

Abstract: This paper addresses and discusses the central issues that researchers have to deal with when conducting crossnational comparative research within the area of egovernment. The issues are classified into two main categories. The first category represents the issues and challenges that may affect the reliability and the quality of data being collected for comparative studies. The second category represents the remaining issues related to the research objective, the selection process of countries and the analytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 18 publications
0
26
0
Order By: Relevance
“…While the above statistics offer a synopsis of e-government adoption and diffusion from a generic perspective, several academic studies have explored e-government acceptance in the United States (Carter & Weerakkody, 2008;Welch et al, 2005), the UK (Carter & Weerakkody, 2008;Dwivedi et al, 2006;Sipior et al, 2011) and at a cross-country level (see for instance (Gharawi, Pardo, & Guerrero, 2009;Luna-Reyes et al, 2010;Srivastava & Teo, 2007). However, our research found no scholarly studies that have examined the crossnational adoption of the same 'transformed' public (e-government) service.…”
Section: Cross-country Research On E-government Adoptionmentioning
confidence: 86%
“…While the above statistics offer a synopsis of e-government adoption and diffusion from a generic perspective, several academic studies have explored e-government acceptance in the United States (Carter & Weerakkody, 2008;Welch et al, 2005), the UK (Carter & Weerakkody, 2008;Dwivedi et al, 2006;Sipior et al, 2011) and at a cross-country level (see for instance (Gharawi, Pardo, & Guerrero, 2009;Luna-Reyes et al, 2010;Srivastava & Teo, 2007). However, our research found no scholarly studies that have examined the crossnational adoption of the same 'transformed' public (e-government) service.…”
Section: Cross-country Research On E-government Adoptionmentioning
confidence: 86%
“…While a cross-country analysis suffers from many shortcomings, including data reliability, matching of samples, time frames and methods of data collection (Jowell 1998;Gharawi et al 2009), a within-country analysis of resource curse is less common (Caselli andMichaels 2013, Fleming et al 2015;James 2015). Focus on a within-country analysis permits the analysis to overcome concerns regarding endogeneity (Cust and Poelhekke 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Certain data quality approaches were followed to deal with the main challenges associated with cross national comparative research: the language of data collection, the translation process, the matching of samples, the timing of data collection, and the consistency of the research process and instruments [29]. The two cases used the same interview protocol to ensure consistency and respondents were interviewed in their native languages.…”
Section: Methodsmentioning
confidence: 99%